Ethical codes as instruments for cooperative sustainability / Nooraslinda Abdul Aris … [et al.] - Abdul Aris, Nooraslinda; Othman, Rohana; Abdul Rahman, Safawi; Marzuki, Marziana Madah; Wan Chik, Wan Mohd Yusof (Penerbit UiTM (UiTM Press), 2016)
Numerous ethical breaches have made cooperatives, and their management endures pressure to improve their image and ethical performance. One of the ways identified is by adopting ethical codes. Codes are regarded as instruments to enhance social responsibility that contain open guidelines describing desirable behavior and closed guidelines prohibiting certain behaviors. Codes clarify the norms and values organizations seek to uphold. Regarded as social enterprises, cooperatives are compelled to scale up their operations for sustainability reasons towards positive contribution to the national economy. Past research on ethical codes affecting behavior, attitude and performance has yielded mixed results. In addition, there are very few studies devoted to cooperatives. This paper presents the results of scientific literature, highlighting how ethical codes and sustainability may progressively improve the cooperatives' image and reputation in the eyes of the stakeholders.